Combined Effects Of Eurycoma Longifolia And Calcium On Bone Metabolism Of Orchidectomised Male Rats - Nadia Mohd Effendy; Ahmad Nazrun Shuid (Universiti Kebangsaan Malaysia, 2024)
Osteoporosis is characterized by low bone mass and destruction of bone microarchitecture. Androgen deficiency or hypogonadismisone of the major risk factors of osteoporosis in men. Testosterone replacement therapy (TRT) is the main treatment for hypogonadal osteoporosis but may cause side effects such as prostate cancer and cardiovascular diseases. An alternative treatment is required, with similar efficacy but minimal side effects. Eurycoma longifoliais a herbal plant that may have potential in treating osteoporosis, especial-ly if it is supplemented with calcium. This study was conducted to determine the combinational effects of Eurycoma longifoliaand cal-cium on the bone markers and biomechanical strength of orchidectomised male rats. A total of 48 rats were randomly divided into 6 groups; sham-operated control (SHAM), orchidectomised control (ORX), orchidectomised + 8mg/kg testosterone (TES), orchidecto-mised + 15mg/kg Eurycoma longifolia(EL), orchidectomised + 1% calcium (Ca) and orchidectomised + combination of 15mg/kg EL and 1% calcium (EL+Ca). Treatment was given for a period of 6 weeks and blood samples were taken prior and after the treatment to measure osteocalcin and CTX levels. The rats were euthanized after 6 weeks and femora were dissected for biomechanical analysis.The osteocalcin levels did not show any significant changes, while the CTX levels were significantly increased in the ORX group but de-creased in the other groups. The strain parameter of the EL+Ca was significantly lower than the EL group. In conclusion, single supple-mentation of EL was better than combination with calcium in terms of the bone remodeling and strength of orchidectomised rats.